Capital liberalization and the US external imbalance - Elvira Prades; Katrin Rabitsch (Magyar Nemzeti Bank, 2009)
Differences in financial systems are often named as a prime candidate for the current state of global imbalances. This paper argues that the process of capital liberalization can explain a substantial fraction of the US net external liabilities. We present a simple two-country model with an internationally traded bond, in which capital controls are reflected in the presence of borrowing and lending constraints on that bond. In a US versus the rest of the world (RoW) scenario, we perform experiments that are largely consistent with countries' liberalization experiences. A reduction in the RoW's controls on capital outflows and/or a tightening in the RoW's borrowing constraint enables the US economy to better insure against consumption risk relative to the rest of the world, and therefore decreases its motives for precautionary asset holdings relative to the rest of the world. As a result of these asymmetric shifts in countries' barriers to capital mobility, the US runs a long run external deficit.
Keywords: F32; F34; F41; 330; Capital Liberalization; External Imbalances; Net Foreign Asset Position; Precautionary Savings; Borrowing and Lending Constraints; Finanzmarktregulierung; Kapitalverkehrskontrolle; Kapitalmobilität; Außenwirtschaftliches Gleichgewicht; Leistungsbilanz; USA; Welt